O uso pedagógico do computador e da internet - Vanz, Gerson (2015)
This research is based in a case study that verified how the computer and the Internet are being used as sources to the Geography classes, in the Paranaense public school, in the cities of Pato Branco, Francisco Beltrão and Itapejara D Oeste, located in Southwest of Paraná. The data collection was realized in two periods: in 2013 with teachers and students and then, in 2014 with principals and pedagogues of the schools: Colégio Estadual Pato Branco EFM in Pato Branco, Colégio Estadual Mário de Andrade EFM in Francisco Beltrão and Colégio Estadual Castelo Branco EM in Itapejara D Oeste. Initially we highlight the importance of the cultural factor and of the historic factor in education based on the Historical Cultural theory of Vygostky and the elements that justify it, highlighting the role of the teacher as a mediator in the use of the Information and Communication Technologies (ICTs). In a second moment, we highlight the public politics that were created to enplane the Information and Communication Technologies (ICTs). Among the public politics that we are going to highlight, in the federal level, there is the project EDUCOM (Education with Computers), the programs as PRONINFE (National Program of Educational Data Processing), PROINFO (National Program of Data Processing in Education), PBLE (Broadband at Schools Program) and PROUCA (A Computer for Student Program). Referring to public politics implemented in the state level, in Paraná, there is the project BRA 03/036 (Basic Education and Digital Inclusion in the State of Paraná Program), PRD (Digital Paraná Program) and dia a dia Educação gateway. Finally, we present the data and results of this survey with debate about the use of technologies in the public schools based in the vision of the subjects, teachers, students, principals and pedagogues, ending with some considerations about public politics and their real implantation in schools, mainly in the use of computer and internet. A series of questions that are presented interfere in the pedagogic use of computer and internet in the public schools.